The Ottoman Enlightenment: Geography and Politics in the Seventeenth- and Eighteenth-Century Ottoman Empire. (November 2019) - Emiralioğlu, Pınar
This article investigates the close relationship between geographical knowledge and imperial politics in the Ottoman Empire during the seventeenth and eighteenth centuries. Through an analysis of an anonymous portolan chart from 1652 and geographical accounts of Katip Çelebi, Ebu Bekir b. Behram el-Dimaşki and Osman b. Abdülmennan, it examines the circulation of 'geography' and 'geographical knowledge' in the Ottoman Empire during the seventeenth and eighteenth centuries. In doing so, it aims to integrate the Ottoman Empire into the recently developing historical treatment of Enlightenment as a response to cross-border interaction and global integration. According to the traditional understanding, Ottoman involvement with modern science and technology did not begin until the nineteenth century when the Ottoman state enacted a series of reforms in education, economy, and military. This article aims to challenge this traditional understanding and argues that Ottoman ruling elites and scholars did indeed participate in intellectual discussions and political developments of the seventeenth and eighteenth centuries. The knowledge exchange between the Ottoman geographers and their European contemporaries during this period laid the foundations of what I call 'the Ottoman Enlightenment.' The works discussed in this article informed the Ottoman imperial court and literate urbanites of the changes in the spatial understanding of the world and of the universe while also helping them to reevaluate the role of the Ottoman Empire globally during a period typically regarded as the beginning of Ottoman decline.